2018
DOI: 10.1182/bloodadvances.2018020552
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of joint hemorrhages and procedures in nonsevere hemophilia A vs B

Abstract: Key Points• Joint hemorrhages and orthopedic procedures are more frequent in patients with hemophilia A than in those with hemophilia B.• FA levels of 20% may be required to prevent all joint hemorrhages.Data are needed on minimal factor activity (FA) levels required to prevent bleeding in hemophilia. We aimed to evaluate associations between hemophilia type and FA level and joint bleeding and orthopedic procedures using longitudinal data. Data were collected over an 11-year period on males with nonsevere hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 32 publications
3
95
0
Order By: Relevance
“…These genes encode proteins that work in concert to contribute to clot formation at a break in a blood vessel wall, and their absence results in prolonged bleeding. Clinical manifestations include severe arthropathy from repeated bleeding into joints, and increased mortality if untreated . An estimated 1 in 5000 males are affected by haemophilia; however, identification of these patients is a challenge, which disproportionately affects developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…These genes encode proteins that work in concert to contribute to clot formation at a break in a blood vessel wall, and their absence results in prolonged bleeding. Clinical manifestations include severe arthropathy from repeated bleeding into joints, and increased mortality if untreated . An estimated 1 in 5000 males are affected by haemophilia; however, identification of these patients is a challenge, which disproportionately affects developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…den Uijl et al assembled observational data showing that a baseline level >12% FA would make non‐traumatic bleeding very unlikely . In another study, Soucie et al found more inter‐individual variability, but found similar results in that individuals with levels above 15% FA had minimal joint bleeding . Therefore, if gene therapy results in high and sustained hemostatic factor activity, as preliminary trials suggest, we would not expect spontaneous bleeding in patients with levels over 15% FA.…”
Section: Do Advanced Therapies Require Further Changes On Use Of Outcmentioning
confidence: 83%
“…89 In another study, Soucie et al found more inter-individual variability, but found similar results in that individuals with levels above 15% FA had minimal joint bleeding. 90 Therefore, if gene therapy results in high and sustained hemostatic factor activity, as preliminary trials suggest, we would not expect spontaneous bleeding in patients with levels over 15% FA. On the other hand, we cannot really predict how many traumatic bleeds one would observe; first, because published data are scanty; second, because traumatic bleeds depend on level and intensity of physical activity, which may vary a lot patient to patient.…”
Section: What Are the Best Outcome Measures In Trials With High Andmentioning
confidence: 99%
“…When we focus on the annual joint bleeding rate (AJBR), a rate of 0.08 (SD ± 0.26) is seen in the cohort study of Tagliaferri et al In contrast, a recent study performed in the United States by Soucie et al, demonstrated a higher AJBR of 0.97 in patients with mild hemophilia A. However, for this latter study the data on joint bleeds were collected through patient‐reported forms, and this may have potentially led to an overestimation of the AJBR due to misclassification of bleeds by patients …”
Section: Bleeding Phenotype In Nonsevere Hemophiliamentioning
confidence: 93%
“…However, for this latter study the data on joint bleeds were collected through patient-reported forms, and this may have potentially led to an overestimation of the AJBR due to misclassification of bleeds by patients. 30 The first detailed study to investigate the association between baseline FVIII levels and the bleeding phenotype was a single-center study from the Netherlands including 377 patients. 31 This study found that the age at first FVIII treatment increased with a higher FVIII level, as the median age at first treatment with FVIII concentrate was 2.9 and 5.5 years in the moderate and mild hemophilia A groups, respectively.…”
Section: Diagnosis Of Nonsevere Hemophiliamentioning
confidence: 99%